Topical safety and vasoconstrictive assay-based bioequivalence of a new reformulated mometasone cream. (3rd July 2017) - Krishna, Rajesh; Horowitz, Ann; Larson, Patrick; Bolognese, James; Marcantonio, Eugene E.
Abstract: Objectives: A new improved mometasone furoate (Elocon™) cream with an emulsification system that produces a stable emulsion has been developed. In order to register the product in various markets, it was essential to ensure the cream was topically well tolerated and that it was bioequivalent to the reference product. Methods: Phase I clinical studies were performed to assess the local safety and tolerability upon multiple dosing of this new cream as well as to assess the single-dose bioequivalence relative to the marketed product. Bioequivalence was assessed using a vasoconstrictive assay (VCA) after a dose-duration pilot study was completed with the marketed Elocon cream. Key findings: The new mometasone cream and its vehicle were nonirritating in healthy subjects during 21-day patch application (MCII <0.025). The positive control was moderately irritating in the same study. The pivotal VCA study enrolled 162 subjects with 105 detectors included in the analysis of bioequivalence. In the 105 detectors, the ratio (×100%) of AUEC values at ED50 for test vs. standard (90% CI) was 112.91% (105.55, 120.87), within the bioequivalence criteria of (80, 125). Conclusions: These studies supported the registration of reformulated mometasone cream in various markets.